Propuesta arquitectónica para una planta de tratamiento de residuos (Neiva, Huila) (2020)
In the city of Neiva, environmental pollution generated by the misuse of organic and inorganic waste is one of the most complex problems that the population has to face; unfortunately, the city does not have the implementation of recycling alternatives from the place of origin, which leads to the waste having inadequate treatment and, in turn, by depositing it in the sanitary landfill, is the reason that it fills up its storage capacity. The purpose of the research is to generate a diagnosis for the development of architectural spaces that allow the use of resources, in order to provide solutions. The population benefiting in general is the city of Neiva, directly the inhabitants of commune nine, increasing the labor index, in addition to mitigating the environmental impact generated through recycling mechanisms. The scope of the project is to propose a plant for the use of solid waste, resulting from the generation of environmental education strategies, to promote recycling in the capital of Huila. It encompasses exploratory, analytical, and descriptive research methodologies.